Connecting the quantum dots. - Sargent, E.H (IEEE spectrum)
In this paper, paints, an optoelectronic materials were used to make better photovoltaic cells, imaging sensors, and optical communication equipment by considering the nanomaterial design understanding at a molecular level. Infrared solar cells from semiconductor quantum dots were developed and the paint-on technology for other device applications were also discussed.